KEKUATAN TERAPI SYUKUR DALAM MEMBENTUK PRIBADI YANG ALTRUIS: PERSPEKTIF PSIKOLOGI QUR’ANI DAN PSIKOLOGI POSITIF - Takdir, Mohammad (Jurnal Studia Insania, 2017)
This paper aims to elaborate the therapy power of gratitude in the shaping of the altruistic personality. This research used a comparative study of quranic psychology and positive psychology as a reference to explain about therapy power of gratitude. This research used a psychological approach to reveal the influence of the grateful on the meaningfulness of life.The results showed grateful in quranic psychology is a form of recognition of the favors bestowed by God with the submission and obedience according to what has been commanded. Gratitude in quranic psychology can be practiced in the three ways, namely orally grateful, heart, and deed. Gratitude in positive psychology is an emotional positive reaction in response to the receipt of a gift and benefit from someone. Gratitude in this perspective can be practiced personally (be thankful to the people who has given a gift) and transpersonal (expression of gratitude to God who has given many gifts in this world). In quranic psychology, be grateful can be Sufi healing or therapy to cure individualistic attitude into the life of the society. In positive psychology perspective, becoming a thankful person tend to be more generous and humble, if compared with those who never grateful.